A randomized trial assessing the effects of health claims on choice of foods in the presence of front-of-pack labels - Talati, Zenobia; Norman, Richard; Kelly, B.; Dixon, H.; Neal, B.; Miller, C.; Pettigrew, Simone (American Society for Nutrition, 2018)
Background: As a public health intervention, front-of-pack labels (FoPLs) have the potential to reach large numbers of consumers and promote healthier food choices. Of the different FoPLs, those that summarize a product's overall nutritional profile tend to be most effective in guiding healthier choices. However, information is lacking as to whether FoPLs are as effective when nutrient or health claims also appear on-pack. Objective: The aim of this study was to examine how the choice of foods of varying levels of healthfulness (less healthy, moderately healthy, and healthier) is affected by the appearance of various FoPLs (Daily Intake Guide, Multiple Traffic Lights, Health Star Rating) when shown in combination with different claim conditions (no claim, nutrient claim, general-level health claim, and higher-level health claim). Design: Adults and children (n = 2069) completed a discrete-choice experiment online. Respondents were shown 8 choice sets, each containing 4 alternatives of the same food type (cookies, cornflakes, pizza, or yogurt) of varying levels of healthfulness and were asked which product they would likely purchase (or they could select none). Respondents were randomly assigned to view 1 of the 3 FoPLs across all choice sets. Claim type and healthfulness varied within choice sets in accordance with a D-efficient design. Results: The probability of choosing a healthy product and avoiding an unhealthy product was greatest when only an FoPL (especially the Health Star Rating) appeared on-pack. The addition of a nutrient or health claim did not affect the likelihood of picking healthier products but did increase the likelihood of selecting less healthy foods across all FoPL conditions. Conclusions: FoPLs are most effective in helping consumers make better food choices when nutrient and health claims are not present. Policies are required to control how nutrient and health claims are applied to less healthy foods. This trial was registered as ACTRN12617000015347 (www.anzctr.org.au/Trial/Resgistration/TrialReview.aspx?id=372055&isReview=true).